Comparison of the Herbal Care Package and Breast Care Method On Volume Of Breast Milk Among Postpartum Mothers With Breast Engorgement - Ihrom Fatma Saputri; Suharyo Hadisaputro; Diyah Fatmasari (Universitas STRADA Indonesia, 2020)
Warm herbal ball compress were alternative treatments on increase volume of breast milk. Cold cabbage leaves to reduce breast pain. Combination of two non pharmacology methods will be more effective to reduce breast pain and increase volume of breastmilk. The study aimed to analyze difference effect of herbal care package than breastcare on breast milk volume.The design study conduct quasi experiment with pretest-posttest with a non-equivalent control group. The subject is 30 postpartum mothers day 1-14 with breast engorgement in Semarang. The intervention group was applied warm herbal ball compresses, breast massage, and cold cabbage. However control group was applied breastcare. Both groups received these treatment 6 times during 3 days with duration of 20 minutes. Electric breast pump and beaker glass was instruments to observed volume of breast milk. The results obtained p-value 0.001. Herbal care package can increase volume of breast milk than breastcare.